Pelatihan Geolistrik Untuk Mendapatkan Potensi Batu Andesit dan Granit di Kecamatan Salatiga Kabupaten Sambas - Fadil Iqbal, Muhammad; Putri Ira, Nurmaya; Mukhtar, Wahdaniah; Cahyadi Saputra, Doddy; Adibah, Fairuz; Aprillia, Ricka; Dhowian Parabi, Ashraf (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2024)
The geoelectric method is an effective geophysical method in subsurface mapping by utilizing the electrical properties of rocks. The basic principle of the geoelectric method is to measure resistivity by flowing an electric current into the earth through electrodes. Geoelectrical (resistivity) surveys generally aim to determine the condition or structure of subsurface geology based on variations in rock type resistance. The results of the training showed significant variations in the resistivity of Andesite and Granite rocks, which were indicated as potential resource zones worthy of further exploration. The results of resource potential calculations show that the volume of Andesite is 909,364,491 m³ and the volume of granite is 55,436,878 m³. This training also provides recommendations for residents in Salatiga District, Sambas Regency, to use this as literature to attract investors so they can invest in the area as much as the relevant volume.